Criminogenic Risk Factors and the Onset of Suicidal Intentions in Adolescents Engaging in Deliberate Self-Poisoning: Proposed Hypotheses from Psychiatric Consultation Observations. (Academic Journal of Internal Affairs, 2024)
Aim: Adolescents frequently encounter normative crises that are neither deviant nor pathologically rooted, yet professionals and daily caregivers may sometimes perceive them as such. Deliberate self-poisoning, a prevalent form of suicidal behaviour in adolescents, often coexists with indicators of deviant developmental patterns and family backgrounds suggestive of potential future criminal lifestyles. This study aims to scrutinise the validity of this assumption.Methodology: Employing document analysis, they examined handwritten consultation records and subjected the extracted data to statistical chi-square tests.Findings: The study encompassed 109 cases (88 girls, 21 boys). While criminogenic risk factors were identified in the adolescents’ lives, the majority showed no direct association with suicidal intent or ideation. Exceptions included school drop-out, domestic violence, and bullying, associating with suicidal intent, and bullying alone linked to suicidal ideation. Both intent and ideation were more prevalent among girls.Value: They findings indicate that deliberate self-harm and criminogenic risk factors are largely disconnected. Thus, they emphasise that attributing deviant family backgrounds and future career prospects to adolescents’ self-poisoning is misleading. Professionals within a child’s environment must refrain from such labelling in their daily communication.
Keywords: labeling; deviance; maladaptive development; bullying